On lower separation and regularity axioms in fuzzy topological spaces - Saif, Amin; Kilicman, Adem (Hindawi Publishing Corporation, 2011)
We use the concepts of the quasicoincident relation to introduce and investigate some lower separation axioms such as αT0, T 1, αT1/2, and αT2 as well as the regularity axioms R 0 and R 1. Further we study some of their properties and the relations among them in the general framework of fuzzy topological spaces.